Mineral Identification of Marble Stones From Gunung Kerambil, South Aceh Using X-ray Diffraction - Lindawati Lindawati; Mursal Mursal (PSI-Aceh, 2018)
Penelitian ini bertujuan untuk mengetahui kandungan mineral pada batu marmer dari kawasan Gunung Kerambil, Aceh Selatan. Kandungan mineral diidentifikasi menggunakan alat difraksi Sinar-X (XRD) dengan sumber radiasi CuKa dengan panjang gelombang 1.540600 Å. Penentuan kandungan mineral dilakukan berdasarkan puncak difraksi hubungan antara sudut (2θ) dan intensitas (I) difraksi. Berdasarkan hasil analisa data, tiga puncak difraksi tertinggi ditunjukkan pada sudut difraksi (2θ) = 29,5029o; 26,5997o dan 47,5998o dengan Intensitas sebesar 5059, 1283 dan 503. Secara umum, mineral yang diidentifikasi pada batu marmer dari Gunung Kerambil adalah jenis Kalsit (CaCO3). Kandungan mineral dari suatu batuan sangat dipengaruhi oleh formasi geologi kawasan tersebut. The purpose of the study was to determine the mineral content of marble stones from the Gunung Kerambil area, South Aceh. Mineral content was identified using X-Ray Diffraction equipment (XRD) with CuKa radiation with a wavelength of 1.540600 Å. Determination of mineral content is carried out based on the diffraction peaks of the relationship between diffraction angles (2θ) and intensity (I). Based on data analysis, the three highest diffraction peaks were shown at diffraction angles (2θ) of 29.5029o; 26.5997o and 47.5998o with Intensity (I) of 5059, 1283 and 503, respectively. In general, the minerals identified in marble sample from Gunung Kerambil were Calcite (CaCO3). Mineral content of a rock is strongly influenced by the geological formation of the region. Keywords: Mineral, Batu Marmer, XRD, Gunung Kerambil, Aceh Selatan